2019
DOI: 10.3390/su11051406
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Gold from Chloride Solution by TEMPO-Oxidized Cellulose Nanofiber Adsorbent

Abstract: The goal of this study was to assess the sustainability of a modified cellulose nanofiber material for the recovery of precious gold from chloride solution, with a special focus on gold recovery from acidic solutions generated by cupric and ferric chloride leaching processes. TEMPO-oxidized cellulose nanofiber in hydrogel (TOCN), dry (H-TOCN, F-TOCN) and sheet form (S-TOCN) was examined for gold adsorptivity from chloride solution. Additionally, this work describes the optimum conditions and parameters for gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Given the increasing number of environmental accidents due to the application of these gold-recovery technologies, scientists are looking for environmentally friendly technologies, such as adsorption [ 18 ]. The recovery process only makes sense if the cost of recovery is much lower than the value of the recovered gold.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing number of environmental accidents due to the application of these gold-recovery technologies, scientists are looking for environmentally friendly technologies, such as adsorption [ 18 ]. The recovery process only makes sense if the cost of recovery is much lower than the value of the recovered gold.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method for extracting gold is dissolving it in aqua regia, but this process has critical steps, like evaporation of HCl and HNO 3 . The use of halides like the chlorine gas method is used mostly in the industrial application to dissolve gold and produce stable gold chlorides [45,46]. Shirin et al [47] proposed this method of dissolving gold by using the chlorine gas to synthesise a pure gold chloride solution, which can use the final product directly in the USP process.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, CNs were reported to effectively coordinate and absorb several heavy metal cations, for example, Cu (II), Co (II), Cd (II), Ni (II), Pb (II), As (V), and Cr (VI) cation. Jafari et al also demonstrated the ability to efficiently adsorb gold from a chloride solution (98%) [50]. Ma et al further reported the ability of CNs to remove radioactive uranyl ions (UO22+), from solutions caused by the affinity of UO22+ ions with the carboxylate groups, and the maximum adsorption capacity 167 mg•g −1 is 2-3 times greater than traditional adsorbents (e.g., silica particle, montmorillonite) [51].…”
Section: Absorbents In Water Treatmentmentioning
confidence: 99%